Strabismus surgery innovative and classic approaches - Ludwig, Irene H. (Thieme, 2021)
"Strabismus correction is the third most common ophthalmic surgery in the US, with 1.2 million procedures performed each year. Strabismus Surgery : Innovative and Classic Approaches by renowned pediatric ophthalmologist Irene H. Ludwig provides comprehensive coverage of strabismus treatment - featuring state-of-the-art techniques based on recent anatomical research and discoveries. Throughout the text and accompanying videos, an impressive group of contributors share clinical pearls and firsthand knowledge"--